THE ROLE OF WOMEN’S RIGHTS PROTECTION IN SOCIETY - Rano Abduvaitova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the importance of protecting women’s rights in society, its impact on social development, and its legal foundations. Ensuring women’s rights is directly linked to gender equality, economic development, political stability, and social justice. The article examines the effective mechanisms for the protection of women’s rights based on the experiences of various countries, international legal norms andnational legislation.